Beyond the 'big four': Venom profiling of the medically important yet neglected Indian snakes reveals disturbing antivenom deficiencies. - R R Senji Laxme; Suyog Khochare; Hugo Francisco de Souza; Bharat Ahuja; Vivek Suranse; Gerard Martin; Romulus Whitaker; Kartik Sunagar (Public Library of Science (PLoS), 2019)
BACKGROUND:Snakebite in India causes the highest annual rates of death (46,000) and disability (140,000) than any other country. Antivenom is the mainstay treatment of snakebite, whose manufacturing protocols, in essence, have remained unchanged for over a century. In India, a polyvalent antivenom is produced for the treatment of envenomations from the so called 'big four' snakes: the spectacled cobra (Naja naja), common krait (Bungarus caeruleus), Russell's viper (Daboia russelii), and saw-scaled viper (Echis carinatus). In addition to the 'big four', India is abode to many other species of venomous snakes that have the potential to inflict severe clinical or, even, lethal envenomations in their human bite victims. Unfortunately, specific antivenoms are not produced against these species and, instead, the 'big four' antivenom is routinely used for the treatment. METHODS:We characterized the venom compositions, biochemical and pharmacological activities and toxicity profiles (mouse model) of the major neglected yet medically important Indian snakes (E. c. sochureki, B. sindanus, B. fasciatus, and two populations of N. kaouthia) and their closest 'big four' congeners. By performing WHO recommended in vitro and in vivo preclinical assays, we evaluated the efficiencies of the commercially marketed Indian antivenoms in recognizing venoms and neutralizing envenomations by these neglected species. FINDINGS:As a consequence of dissimilar ecologies and diet, the medically important snakes investigated exhibited dramatic inter- and intraspecific differences in their venom profiles. Currently marketed antivenoms were found to exhibit poor dose efficacy and venom recognition potential against the 'neglected many'. Premium Serums antivenom failed to neutralise bites from many of the neglected species and one of the 'big four' snakes (North Indian population of B. caeruleus). CONCLUSIONS:This study unravels disturbing deficiencies in dose efficacy and neutralisation capabilities of the currently marketed Indian antivenoms, and emphasises the pressing need to develop region-specific snakebite therapy for the 'neglected many'.